EL INDIVIDUO Y LA COMUNIDAD EN LA POSMODERNIDAD Y EL GLOBALISMO - Gonzales, Osmar (2019)
The authors verify that exist many meaning about postmodernity and investigate on the idea about individual and the community in this time of globalization. They search to establish a minimal concept about postmodernity that connect it to a thinking that recover the human sense of actual reflection.